FDI to Africa : The Role of Price Stability and Currency Instability - Reinhart, Carmen; Rogoff, Kenneth (Washington, D.C. : International Monetary Fund, 2003)
Africa lags behind other regions in attracting foreign direct investment (FDI). In some circumstances, there are obvious explanations for the absence of FDI, such as a high incidence of war. In this paper, we examine the role that monetary and exchange rate policy may have played in explaining this outcome. Specifically, we document the incidence of inflationary episodes and currency crashes in order to compare countries within the region as well as to make comparisons with other regions. Furthermore, since monetary policy can range from very transparent to very opaque, we assess Africa's track record with dual and parallel markets. We use the parallel market premia as an indicator of the degree of distortions and extent of transparency. Our findings suggest that this is a promising line of inquiry because Africa does stand apart from other regions in this measure of transparency. We also discuss some of the fiscal underpinnings of Africa's bouts with high inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet